Розрядні процеси в зерновій масі під дією сильного електричного поля імпульсного струму - Усенко, С. М.; Науменко, О. В. (Energy and Automation, 2017)
DISCHARGE PROCESSES IN THE GRAIN MASS UNDER APPLYING OF HIGH ELECTRIC FIELD OF PULSE CURRENT S. Usenko, O. Naumenko An important factor that leads to losses of grain storage is the activity of insect pests of grain reserves. To destroy pests mainly used fumigants that are quite toxic. An alternative method is ozone, but modern uses of ozone is energy-consuming and inefficient due to the loss of ozone in its submission of ozone generator to the grain and the uneven treatment. The department developed electrotechnologies and electric equipment and devices in which ozone formation occurs directly in the grain mass under the influence of a strong electric field. Studies have shown the possibility of using this method to control pests of grain. The concentration of ozone in the air gap grain mass depends on the intensity of ionization processes, especially in the frequency of partial discharge of air inclusions. The intensity of the ionization process varies depending on the strength of EPS. EPS intensity can be increased to a value above which can lead to the breakdown in the grain mass. It is known that the intensity of the ionization process depends on the moisture content of the grain mass. In developed installation can change the pulse frequency of pulsed high voltage source. Therefore, it was necessary to study discharge processes in the grain mass, depending on the moisture content of the grain mass and frequency of pulses pulsed high voltage source. The aim of this work is to study processes bit in the grain mass and establish their patterns depending on the humidity of the grain mass and pulse frequency pulsed high voltage source. The proposed method of processing corn is between plane-parallel plate electrodes to which high voltage is supplied. The peculiarity of this type of treatment is that the grain mass, flora and insect pests, the following factors of influence: strong electric field, surface and volume current ionization processes occurring in the airspace of grain mass air ions and ozone, which is formed under partial discharge. From high voltage pulse source voltage is applied to the plane-parallel electrodes. The walls of the processing chamber is made of dielectric material (plexiglass). Adjusting the voltage provided via autotransformer. In the processing chamber is set insulating plates that separate the wheat from the electrodes. In the range of zero entered resistor wire that fixes the bit currents that flow in grain. The signal is removed with an oscilloscope. The control voltage is made kilovoltmeter current controlled milliammeters. In the scheme provided for adjusting the parameters of pulses of high voltage source. For research samples taken barley varieties "Vakula" moisture content of 12.7 %, 13.3 %, 14 %, 14.7 %. Dimensions camera processing: the distance between the electrodes - 3 cm; electrode length - 10 cm; grain filling height - 6 cm. The article presents the results of research on the effects of humidity on intensity discharge processes in the grain mass. According to the research found that the frequency of discharges in the grain mass depends on the moisture content of grain and has a frequency dependence. The maximum discharge frequency values obtained with humidity values close to conditioning (13.3...14 %). The dependence will determine processing modes depending on the moisture content of the grain mass and parameters of the power supply.